Co‐production in peer support group research with disabled people. Issue 3 (20th April 2018) - Purcal, Christiane; Fisher, Karen R.; Robinson, Sally; Meltzer, Ariella; Bevan, Ngila
Abstract : Peer support action research is a co‐production method used by groups of people with a shared experience, in order to generate knowledge and mutual assistance. This paper analyses co‐production experiences from a recent Australian research project, which formed peer support groups to explore how disabled people were managing their transition to self‐directed support. Using the project as a case study and applying a community participation framework derived from social geography, this paper addresses questions about which collaborative mechanisms strengthen peer support research so that the research process and outputs benefit each of the participants involved. The project used a mixed‐method, co‐production approach. University researchers formed research partnerships with disability community organisations to support the research activity in each Australian state. The community organisations formed peer support groups, facilitated the groups and communicated group processes and findings to the university researchers. The group members and facilitators decided what they wanted to do in the group and how to do it. The academics provided research support, training, a topic guide and resources for group activities. All participants reflected on challenges and lessons learnt and modified the project as it progressed. Both the methods and findings have implications for peer support as co‐productive research. The process enhanced the research capacity of the participants, disability community and academics, and strengthened peer support, advocacy and confidence about self‐directed support. The findings from the peer support groups about their transition to self‐directed support demonstrated their preference for, and trust in, peers as information sources. The regular collective reflections with the facilitators produced an additional level of data collection and analysis that enhanced the quality of the co‐production, enabling greater participant control over design and knowledge generation.